Gender diversity in hospitality and tourism top management teams: A systematic review of the last 10 years. (May 2021) - Russen, Michelle; Dawson, Mary; Madera, Juan M.
Abstract: Due to women still accounting for less than a quarter of hospitality and tourism executive-level positions, the purpose of this paper was to identify antecedents to and outcomes of gender diverse hospitality and tourism top management teams, describe potential mediators and moderators to these relationships, and provide directions for future research. A systematic review of gender diversity in hospitality and tourism top management teams (TMTs) was conducted between the years 2010 and 2020, resulting in 26 articles used for the thematic analysis. Antecedents, outcomes, mediators, and moderators of gender diverse hospitality and tourism TMTs were identified. The results indicated female role models, organizational structure, and organizational support as antecedents, while financial performance, business growth, and human resource outcomes were consequences. The resource advantage theory is proposed as an explanation for each of these relationships. This study fills a gap in previous literature by conducting a review of gender diversity, identifying critical gaps, and proposing an overarching theory. Highlights: Antecedents and outcomes of gender diversity in hospitality and tourism TMTs. Systematic review of the literature on female executives in hospitality and tourism. Theoretical analysis of gender diversity. Directions for future hospitality and tourism gender diversity research.